AN INTEGRATIVE ANALYSIS OF STEREOTYPIC BEHAVIORS IN AUTISM SPECTRUM DISORDERS. A CASE PRESENTATION - CRISTINA S. SĂLĂGEAN; CARMEN COSTEA‐BĂRLUȚIU (Studia Universitatis Babes-Bolyai, 2019)
ABSTRACT. Children with Autistic Spectrum Disorders (TSA) often engage in stereotypical behaviors that greatly impede interaction with the environment and the learning process. Because these behaviors are self‐reinforcing, they are often difficult to reduce. Moreover, for a method to be effective, we believe it is necessary to analyze the context in which they occur and the level of development of the child in each area that may influence the appearance or maintenance of these behaviors, besides analyzing their antecedents, consequences and functions. There are few studies that approach stereotypical behaviors in an integrative perspective. The goal of the current study is to analyze the stereotypical behaviors of a child with ASD from an integrative perspective, including Applied Behavior Analysis (ABA), The Neurosequential Model of Therapeutics (NMT) and Sensory Integration Therapy. This study has a great practical relevance because, based on theoretical foundation, it presents a complex perspective of analyzing the stereotypic behaviors and provides practical recommendations for intervention. Further research could test the hypotheses derived from this case presentation.